Diversity in the Workplace: Evidences from Gulf College, Oman - Velasco, Rodrigo; Villar, Romeo; Lunar, Rowena; Velasco, Venus (Journal of Asian Business Strategy, 2016)
The recent developments in the field of human resource management such as manpower outsourcing led to complex issues on multiculturalism and workforce diversity. On the other hand, increasing globalization requires human resource management keep abreast with diverse cultures, values, beliefs and backgrounds. Therefore, capitalizing on workforce diversity is an important issue for leadership and management today. The paper evaluated the workforce diversity in Gulf College Oman in terms of four (4) dimensions; personality, internal, external and organizational. It also discussed the diversity dimensions affecting workforce personality as well as recessive and progressive diversity dimensions. Descriptive research was employed using a self-made survey tool anchored on ‘Dimensions of Diversity Wheel’ by Gardenswartz & Rowe (2003) and ‘Dimensions of Diversity’ by Compass Point Management Group Inc. (2010). Frequency count, mean, average weighted mean and rank were used to statistically analyze the gathered data. Results show that workforce diversity is highly evident in Gulf College Oman. Therefore, a differentiated employee development plan addressing various issues and concerns on workforce diversity should be developed. Motivational techniques should also be in place to further enhance productivity. The college should set the ‘music’ that transcends all boundaries to unify its people and achieve its goals.